Litter dynamics in signal grass pastures in a silvipasture system and in monoculture - Xavier, Deise Ferreira; Lédo, Francisco José da Silva; Paciullo, Domingos Sávio de Campos; Pires, Maria de Fátima Ávila; Boddey, Robert Michael (Pesquisa Agropecuaria Brasileira, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-hyphenate:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:AR-SA;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> The objective of this work was to evaluate the effect of legume trees and eucalyptus presence on litter dynamics of signal grass pasture (Urochloa decumbens cv. Basilisk). The litter dynamics was studied in a silvipastoril system and in monoculture for 12 months. The experimental design was in randomized blocks with six replicates and five animals per paddock. The existing plant litter and the deposited ones were evaluated. The mean existing litter was 5,038 and 3,944 kg ha-1 in the silvipastoril system and in monoculture, respectively. The silvipastoril system increased significantly the quantities of litter deposited. The quantity of nitrogen deposited in the pasture was greater in the silvipastoril system than in monoculture, 228 and 107 kg ha-1 per year, respectively. The presence of legumes and the eucalyptus in the silvipastoril system provided nitrogen, shown by 13C isotope analysis, and dry matter increases in the litter. Increases in the production of litter rich in nitrogen can contribute for the sustainability of signal pastures in a long run.